2019
DOI: 10.1038/s41598-019-43024-w
|View full text |Cite
|
Sign up to set email alerts
|

Cortical circuit alterations precede motor impairments in Huntington’s disease mice

Abstract: Huntington’s disease (HD) is a devastating hereditary movement disorder, characterized by degeneration of neurons in the striatum and cortex. Studies in human patients and mouse HD models suggest that disturbances of neuronal function in the neocortex play an important role in disease onset and progression. However, the precise nature and time course of cortical alterations in HD have remained elusive. Here, we use chronic in vivo two-photon calcium imaging to longitudinally monitor the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 71 publications
5
41
2
Order By: Relevance
“…Correlated activity argues against cell autonomously elevated activity levels of individual cells but rather point to circuit mechanisms (such as increased synaptic inputs or a lack of inhibition). Interestingly, similar alterations within cortex were also recently described in other mouse models of neurodegenerative diseases (NDs), such as Huntington's disease 37 , potentially indicating that impaired E/I balance constitutes a general feature in NDs. Previous work has reported epileptic discharges in APP transgenic mice primarily seen during low gamma states, which the authors linked to impaired function of particularly parvalbumin (PV) positive interneurons 22 .…”
Section: Aberrant Neuronal Activity Levels Are a Key Feature Of Ad Pasupporting
confidence: 63%
“…Correlated activity argues against cell autonomously elevated activity levels of individual cells but rather point to circuit mechanisms (such as increased synaptic inputs or a lack of inhibition). Interestingly, similar alterations within cortex were also recently described in other mouse models of neurodegenerative diseases (NDs), such as Huntington's disease 37 , potentially indicating that impaired E/I balance constitutes a general feature in NDs. Previous work has reported epileptic discharges in APP transgenic mice primarily seen during low gamma states, which the authors linked to impaired function of particularly parvalbumin (PV) positive interneurons 22 .…”
Section: Aberrant Neuronal Activity Levels Are a Key Feature Of Ad Pasupporting
confidence: 63%
“…Hyperexcitability, and subsequent behavioral impairment, could be due to alterations in the myelination of thalamocortical input, corticospinal output axons, or of local circuitry within primary motor cortex. In neurodegenerative disorders, local circuit processing alterations produce hyperexcitability [58][59][60] , which predicts imminent motor impairments in both human patients and animal models 61,62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, electrophysiological studies in the BACHD mouse model (Gray et al, ) found decreased layer II/III PV‐interneuron excitation and decreased CPN inhibition at 6 months, when behavioral symptoms become evident (Gu et al, ; Spampanato, Gu, Yang, & Mody, ). Interestingly, it was recently shown that R6/2 mice have fewer perisomatic PV‐positive terminals on CPNs than their wild type (WT) counterparts, an observation that was also consistent in HD autopsy brains (Burgold et al, ). Importantly, this reduced inhibition was reflected by increased cortical activity measured with in vivo calcium imaging.…”
Section: Introductionmentioning
confidence: 63%